PENERAPAN METODE POSE TO POSE PADA ANIMASI “LEGENDA BATANG BANGAU” - Afif, Muhammad Sayyid (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2023)
Animating is one part of the 3D animation production stage. Animating stage plays a big role in making an animated movie, because at this stage the movement of the character will be the determinant in delivering the story message in the animated movie. The problem that is often found in this animating process is that the movements made or produced still look stiff and make the story difficult to convey. Therefore, a way is needed so that the animation has a smooth movement and the message can be conveyed well. The pose to pose method is one way that can be used, so that the movement in an animated video or movie becomes smooth while still paying attention to existing animation principles. This research aims to apply the pose to pose method to the animated film